Glutathione Reductase-Mediated Synthesis of Tellurium-Containing Nanostructures Exhibiting Antibacterial Properties - Vasquez-Guzman, C; Arenas-Salinas, F; Muñoz-Villagran, C; Muñoz-Diaz, P; Cornejo-Leiva, F; Pugin, B (American Society for Microbiology, 2014)
Tellurium, a metalloid belonging to group 16 of the periodic table, displays very interesting physical and chemical properties and lately has attracted significant attention for its use in nanotechnology. In this context, the use of microorganisms for synthesizing nanostructures emerges as an eco-friendly and exciting approach compared to their chemical synthesis. To generate Tecontaining nanostructures, bacteria enzymatically reduce tellurite to elemental tellurium. In this work, using a classic biochemical approach, we looked for a novel tellurite reductase from the Antarctic bacterium Pseudomonas sp. strain BNF22 and used it to generate tellurium-containing nanostructures. A new tellurite reductase was identified as glutathione reductase, which was subsequently overproduced in Escherichia coli. The characterization of this enzyme showed that it is an NADPH-dependent tellurite reductase, with optimum reducing activity at 30°C and pH 9.0. Finally, the enzyme was able to generate Te-containing nanostructures, about 68 nm in size, which exhibit interesting antibacterial properties against E. coli, with no apparent cytotoxicity against eukaryotic cells. © 2014, American Society for Microbiology.